Bach, Sonatas BWV 1001, 1003, 1005 – Abordagens Interpretativas na Guitarra - Marques, Maria Paula (2019)
This paper considers the interpretative approaches to Bach’s violin sonatas presented thus far on the guitar and provides an alternative proposal. It includes a systematic presentation of the main characteristics of transcriptions and recordings, and focuses on its interpretative consequences. The analysis I undertook showed some main strategies: addition of notes, modification of rhythmic values, alterations of the original notes, and fingering options that bring forth a particular articulation. The recurrent approach emphasizes the instrument’s harmonic nature. A strong tendency towards the modification of several aspects of the original was manifest as well as a fundamentally idiomatic perspective. These aspects inspired the search for a different interpretative option that follows Bach’s autograph. The challenges brought forth by an interpretation in a harmonic instrument which maintains the original text for a predominantly melodic instrument were questioned. Articulation became a central element in the research and my interpretative practice, and questions regarding Baroque practice were considered in the light of present knowledge. My work brings together musicological and artistic research, since the interpretations’ analysis and the referred practices were fundament and inspiration for the search for new interpretative fields and the development of aspects somehow neglected in these sonatas’ guitar interpretations.